The Labeler as an Influence on Labeling Outcomes - Gingerich, Wallace J. (1978)
Focusing upon labeling processes at the level of interpersonal relations, this paper points out the general inattention to the labeler as an influence on labeling outcomes. In addition, recent empirical findings suggest not only that labeler variables may be associated with outcomes, but that different labelers are influenced in different ways by different factors in their interpersonal labeling. Consequently, an effort is made to incorporate knowledge from social perception theory into the labeling perspective in order to enhance our understanding of interpersonal labeling processes. Several labeler related variables which might be expected to influence labeling outcomes are suggested